Confronting gender stereotypes in sports vocational education: a case study - Marcen, Celia; Gil-Pablo, Violeta; Cuadrado-Santañes, María Isabel; Rapún-López, Marta (Frontiers in Sports and Active Living, 2025)
This study explores the impact of a training workshop on gender equality among vocational training students in teaching and social and sports activities in Aragon, Spain. The evaluation of attitudes, beliefs and gender stereotypes related to leadership in sports was conducted on the basis of an analysis of pre- and post-intervention surveys. The methodology incorporated participatory techniques such as brainstorming, killer data and gamified interactive tools, with the objective of encouraging critical reflection and active learning. The results indicate that, although no statistically significant changes were observed, there was an improvement in the Egalitarianism Index (+0.51) after the workshop, especially among female participants. Furthermore, cluster analysis revealed a shift towards attitudes that are more homogeneous and favourable towards equality. The study concludes that this type of intervention has the potential to raise awareness among future sports professionals about structural inequalities and gender stereotypes, and highlights the importance of incorporating specific equality content into vocational training curricula. Notwithstanding the constraints imposed by the sample size and duration, this experience is presented as a promising pedagogical proposal that can be replicated in other educational contexts.